The relationship between shallow anomalies and gas-flaring on the flank of the Nordkapp Basin in the SE Barents Sea - Haldorsen, Joakim (UiT Norges arktiske universitet, 2020)
This study investigates the north-east-subbasin of the Nordkapp Basin in the Barents Sea. Main focus has been on mapping shallow seismic anomalies from 3D data, their potential association with faulting and sub-surface structures, and further to compare the occurrence of seismic anomalies to possible gas-flares above the seabed from water column data. The stratigraphic intervals from Triassic to Cretaceous have been mapped and several seismic anomalies interpreted to be bright spots are identified. The majority of the anomalies are observed in the Cretaceous Kolmule- and Kolje formations, and several are associated with rotated fault blocks giving rise to structural closures (structure A and B) along the Thor Iversen Fault Complex. A possible meteorite impact crater is observed within the Kolmule Formation, suggested to form during Early Albian and is referred to as structure C. Bright spots were observed along the flanks of this structure. Water column data suggest, no gas flares observed above structure A-C, which could indicate that these structures are sealing. In total, seven lines with gas flares was observed, associated with shallow faults, truncations and shallow anomalies. The potential gas flares had a relatively weak amplitude, suggesting a corresponding weak gas flow and might indicate low concentration/supply of gas or sealing of potential gas migrating upwards. Locally, other seismic amplitude anomalies were identified below the URU/seafloor, however still without clear observations of gas flares in the water column above. A possible explanation for this lack of gas flares above such shallow anomalies, might suggest that glacigenic sediments, usually dense and mudrich, could in places act as an impermeable barrier for gas into the water.